Spinal Canal Stenosis - Manfrè, Luigi (New Procedures in Spinal Interventional Neuroradiology, 2016)
This easy-to-consult guide describes new minimally invasive procedures for the treatment of spinal canal stenosis that are accompanied by fewer complications and side-effects, reduce the risks of anesthesia, and lower costs. Clear accounts are provided of various CT and X-ray guided techniques for lumbar spinal canal and foraminal stenosis, including the use of spacers and minimally invasive lumbar decompression (MILD). Helpful introductory information is also provided on biomechanics and symptoms. Like other books in the Springer series New Procedures in Spinal Interventional Neuroradiology, this practice-oriented volume will fill a significant gap in the literature and meet the need expressed by a large number of specialists (interventional neuroradiologists and radiologists, neurosurgeons, and orthopedists) for a topical and handy guide that specifically illustrates the presently available materials and methods.